THE RELATIONSHIP OF SERVICE QUALITY, WORD-OF-MOUTH, AND REPURCHASE INTENTION IN ONLINE TRANSPORTATION SERVICES - S.E., Leonnard (Journal of process management and new technologies, 2017)
Sophisticated and ever-evolving technology enacts many companies use and utilize technology as a mean of delivering innovative and creative new services. Technological developments are widespread in various fields and one of them is in the field of online transportation. The high demand for fast and efficient transportation modes causes the companies engaged in the sector by providing online transportation services are increasing. High competition and large number of drivers require the companies to focus highly on providing high quality services to maintain and increase the number of consumers. This study aims to analyze the effect of service quality on word-of-mouth and repurchase intentions to 80 consumers of online transportation in Indonesia. Partial Least Square Structural Equation Model (PLS-SEM) was employed to analyze the data. The results signifies that there is a positive relationship between service quality to word-of-mouth and repurchase intention. Similarly, word-of mouth significantly influences repurchase intention. Further managerial implications are discussed.